General or intentional nature of the dog ownership fee? - Paweł Majka; Tomasz Brzezicki; Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
The fee for owning dogs is not of key importance for a local government unit. This fee is of a general nature and its nature not questioned. However, you can comply with the nature of this fee using simple legislative solutions. Doing so, may result in solving the problem of community control. Currently, there is no discussion as to the purpose of the fees and the methods of spending them.